Traditional Chinese mind–body practices and depressive symptoms in university students: a multilevel dose–response meta-analysis - Yuming Zhang; Shaoyang Hu; Yonghua Liu; Haoran He; Jiajun Lan; Zhikai Qin (Frontiers in Psychology, 2026)
Objective Numerous meta-analyses have evaluated Tai Chi, Qigong and related traditional Chinese mind–body practices (TCMBPs) for depressive symptoms across broader populations; however, to our knowledge, no previous meta-analysis has focused specifically on university students. We therefore aimed to estimate the average effect of TCMBPs on depressive symptoms in this population using a three-level model that explicitly accounts for dependent effect sizes, and to explore nonlinear dose–response patterns and Bayesian cumulative exposure. Methods PubMed, Web of Science, PsycINFO, the Cochrane Library and CNKI were searched from inception to 29 December 2025 for randomized controlled trials. Effect sizes were synthesized with a three-level random-effects model. Heterogeneity, small-study effects and influential estimates were examined using prespecified diagnostics, sensitivity analyses and cluster-robust variance estimation. Subgroup, meta-regression and Bayesian dose–response analyses were treated as exploratory. Results Fifteen randomized controlled trials met the eligibility criteria. After influence diagnostics, the pooled estimate indicated lower depressive-symptom scores after traditional Chinese mind–body practice (SMD = −0.56, 95% CI − 0.84 to −0.27; p < 0.001), although heterogeneity was substantial and the certainty of evidence was moderate. The estimate was similar with cluster-robust variance estimation. Subgroup patterns differed by practice, comparator and participant characteristics, but most contrasts were supported by few studies. Bayesian models placed the lowest fitted effect near a cumulative dose of 33.7 h; this estimate arose from sparse and uneven exposure data and should not be interpreted as a prescriptive optimum. Conclusion Traditional Chinese mind–body practices were associated with a moderate average reduction in depressive symptoms and may be feasible complements to university mental-health programs. Because the evidence was heterogeneous, concentrated in China and of moderate certainty, the findings do not establish equivalent benefits across practices or a recommended dose. Larger, better-reported randomized trials are needed. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/view/CRD420251275476 , identifier PROSPERO (CRD420251275476).